1988
DOI: 10.1083/jcb.106.6.1831
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of mutant low density lipoprotein receptors that fail to reach the Golgi complex.

Abstract: Abstract. In the low density lipoprotein (LDL) receptor system, blocks in intracellular movement of a cell surface receptor result from naturally occurring mutations. These mutations occur in patients with familial hypercholesterolemia. One class of mutant LDL receptor genes (class 2 mutations) produces a receptor that is synthesized and glycosylated in the endoplasmic reticulum (ER) but does not reach the cell surface. These receptors contain serine/threonine-linked (O-linked) carbohydrate chains with core N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 33 publications
(59 reference statements)
4
35
0
Order By: Relevance
“…poorly (Baenziger & Fiete, 1979). The initial sugar of Olinked glycans is added in the ER (Pathak et al, 1988;Tooze et al, 1988). It has recently been shown that E2, but not E 1, contains O-linked glycans (Lundstr6m et al, 1991 ;; in agreement with this, we found that E2, but not E 1, bound to the O-glycan-specific lectin Jacalin (not shown).…”
Section: E2 Is Required For Transport Of E1 To the Golgi Apparatus Busupporting
confidence: 75%
“…poorly (Baenziger & Fiete, 1979). The initial sugar of Olinked glycans is added in the ER (Pathak et al, 1988;Tooze et al, 1988). It has recently been shown that E2, but not E 1, contains O-linked glycans (Lundstr6m et al, 1991 ;; in agreement with this, we found that E2, but not E 1, bound to the O-glycan-specific lectin Jacalin (not shown).…”
Section: E2 Is Required For Transport Of E1 To the Golgi Apparatus Busupporting
confidence: 75%
“…The heterologous expression system in X. laevis oocytes has been shown to be an excellent tool for a robust expression and reproducible expression of NKCC2 proteins. However, it has also been shown for several mutated proteins that, whereas they are completely retained in the ER when expressed in mammalian cells (41)(42)(43), such ER-retained proteins are often transported to the plasma membrane of oocytes to some extent. For example, the ER-retained cystic fibrosis transmembrane conductance regulator lacking Phe-508 (CFTR-⌬F508) confers chloride conductance in oocytes, but it does not exit the ER in mammalian cells (44 -46).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes of initial 0-glycosylation have been found highly enriched in membranes derived from the Golgi apparatus (1,7,8,23), and the sugar nucleotides UDP-GalNAc, UDP-Gal, CMP-NeuNAc, and GDP-Fuc have been shown to be translocated predominantly into Golgi vesicles (26,43). On the other hand, 0-glycosylation of glycoprotein produced by gastric surface cells has been found to be initiated cotranslationally (50); studies with mutant LDL receptor (38). with proglucagon (39, and with El protein of mouse hepatitis virus A-59 (53) indicate that the synthesis of GalNAc-serinelthreonine linkages is an early event and occurs in a pre-Golgi compartment.…”
Section: Discussionmentioning
confidence: 99%